Effect of Skin Model on In Vitro Performance of an Adhesive Dermally Applied Microarray Coated with Zolmitriptan. (3rd June 2018) - Ameri, Mahmoud; Lewis, Hayley; Lehman, Paul
Abstract : Franz cell studies, utilizing different human skin and an artificial membrane, evaluating the influence of skin model on permeation of zolmitriptan coated on an array of titanium microprojections, were evaluated. Full thickness and dermatomed ex vivo human skin, as well as a synthetic hydrophobic membrane (Strat-M®), were assessed. It was found that the choice of model demonstrated different absorption kinetics for the permeation of zolmitriptan. For the synthetic membrane only 11% of the zolmitriptan coated dose permeated into the receptor media, whilst for the dermatomed skin 85% permeated into the receptor. The permeation of zolmitriptan through full thickness skin had a significantly different absorption profile and time to maximum flux in comparison to the dermatomed skin and synthetic model. On the basis of these results dermatomed skin may be a better estimate of in vivo performance of drug-coated metallic microprojections.